Vegetation structure and composition of the montane zone of Mount Gede Pangrango National Park - ARRIJANI ARRIJANI (Society for Indonesian Biodiversity, 2008)
The objective of this study was to found on composition and structure of vegetation of upstream Cianjur Watersheds at the montane zone Mt. Gede Pangrango National Park. Research sampling conducted by using plot method placed purposive random sampling at research location with increase elevation equal to 300 m from sea level. Every 300 m elevation level, were taken 10 sample plots so that up to 1600- 2400 (montane zone) totalize plot were 30. Measured parameter cover density, frequency, dominancy, Important Value Index (IVI), Diversity Index (H'), and Evenness (E). The subdividing pattern plot had been done through cluster analysis. Result of research indicatethat species puspa (Schima wallichii) and rasamala (Altingia excelsa) were two species with highest Important Value Index, so that both species considered to be dominant the community. The species diversity index (Hâ€™) equal to 3.78 categorized to high, but the evenness value (E) was categorized to low (1.26). The phenomena happened because the distribution of species was heterogeneous. The Cluster Analysis indicated that there were three sub-groups which can be categorized as sub-zone in sub-montane zone were the sub-zone lower, middle and high.Â© 2008 Jurusan Biologi FMIPA UNS SurakartaKey words: structure and composition, vegetation, montane zone, Mt. Gede-Pangrango National Park.